Health care and teaching in the postmodern period considering the conditions of the individual (Research, Society and Development, 2022)
This work aims to reflect on health care and teaching in the postmodern period, considering the individual conditions of the human being. The conditions of the individual consider everything that holistically encompasses the subject, such as their physical and mental health, family and social role, spiritual well-being, and other diverse social determinants of health and education. In the postmodern world, it is clear that there is a lot of emphasis on humanized care and quality teaching, where the patient is the protagonist of the care itself and the student of the teaching-learning process itself. Other nuances and interfaces between health and education have been highlighted and explored. As a result, closer relationships have been established between education, health, environment and social learning. The divergent ideas of the different actors and protagonists of health and education continually clash. These clashes generate discussions, studies, and new experiences.